Transferring skills, transforming careers: examining second career teachers - Reyhan Aslan; Betil Eröz (Humanities & Social Sciences Communications)
Abstract This study explores the transition experiences of second-career teachers (SCTs) who bring professional expertise from non-teaching fields into their roles as educators. While prior professional experiences can offer transferable skills, this research identifies specific challenges SCTs face, especially in acquiring pedagogical content knowledge and adapting to the complexities of teaching. Using a narrative inquiry approach, the study examines the experiences of two SCTs through in-depth interviews. This qualitative method facilitates a comprehensive exploration of their journeys and the complexities involved in becoming foreign language teachers. The interviews reveal that SCTs’ previous knowledge and skills can both empower and hinder their professional development. Although SCTs bring diverse expertise from previous careers, the findings indicate that this professional background does not automatically lead to effective teaching. Instead, the study highlights the difficulties they encounter, such as acquiring pedagogical content knowledge and managing the complexities of their teaching roles. By examining the narratives of two SCTs in a Turkish university context, this paper contributes to our understanding of the interplay between personal and professional factors during career transitions. Additionally, it offers implications for teacher education programs tailored to SCTs. This research adds to the limited literature on SCTs in foreign language education, emphasizing their potential to alleviate teacher shortages. It provides insights into the unique challenges and opportunities SCTs face, offering valuable implications for teacher recruitment and professional development strategies in high-demand areas. Further research on SCTs is recommended to fully understand their impact and support their successful integration into the teaching profession.